Evaluating the Extent and Nature of ‘Envelope Wages’ in the European Union: A Geographical Analysis - Williams, Colin C. (European Spatial Research and Policy, 2009)
To evaluate the spatialities of the illegal wage practice where employers pay their declared employees both an official declared wage and an undeclared ‘envelope’ wage so as to avoid tax liabilities, a 2007 survey conducted in 27 European Union (EU) member states is reported. The finding is that 5% of employees received envelope wages which amount on average to some two-fifths of their wage packet. Revealing how, although heavily concentrated in a small group of East-Central European nations, this wage practice is nonetheless ubiquitous, the paper concludes by discussing how this practice might be tackled.